Treatment with omega-3 PUFAs does not increase the risk of CYP2E1-dependent oxidative stress and diabetic liver pathology - Maksymchuk, Oksana; Shysh, Angela; Stroy, Dmytro (Frontiers in Endocrinology, 2022)
An increase in CYP2E1 expression is a key factor in the development of diabetic oxidative liver damage. Long-term treatment with omega-3 PUFAs, which are CYP2E1 substrates, may affect CYP2E1 expression in the liver. In this work, we performed Western blot analysis, biochemical methods, and microscopic ultrastructural studies of the liver in a streptozotocin-induced rat model of type 1 diabetes to investigate whether long-term treatment with omega-3 PUFAs could induce CYP2E1-dependent oxidative stress and diabetic liver pathology. Significant hyperglycemia and lack of natural weight gain were observed in the diabetic rats compared to nondiabetic controls. A 2.5-fold increase in CYP2E1 expression (protein content and activity) was also observed in the diabetic rats. In addition, signs of oxidative stress were found in the liver of the diabetic rats. Significant increase in transaminases and GGT level in blood serum was also observed, which could indicate marked destruction of liver tissue. Diabetic dyslipidemia (increased triacylglycerol levels and decreased HDL-C levels) was found. Treatment of the diabetic animals with an omega-3-enriched pharmaceutical composition of PUFAs had no effect on CYP2E1 levels, but contributed to a 2-fold decrease in enzyme activity. The intensity of lipid peroxidation also remained close to the diabetic group. But at the same time, antioxidant protection was provided by induction of antioxidant enzyme activity. Examination of the liver ultrastructure revealed no characteristic signs of diabetic pathology. However, omega-3 PUFAs did not normalize blood glucose levels and serum lipid profile. Thus, long-term treatment of diabetic rats with omega-3 PUFAs does not increase the risk of CYP2E1-dependent oxidative stress and development of liver pathology, but prevents some diabetic ultrastructural damage to hepatocytes.